2017
DOI: 10.1097/mnm.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

The role of PSMA PET/CT imaging in restaging of prostate cancer patients with low prostate-specific antigen levels

Abstract: PET/CT with Ga-PSMA is a valuable tool for assessing recurrence of PCa with a high sensitivity in patients who have PSA levels between 0.2 and 5 ng/ml. In addition, this study suggests that PSMA PET/CT can be used in patients with very low (<0.2 ng/ml) but increasing PSA levels, which, in many cases, may influence further clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Schmidt-Hegemann et al reported 129 men with recurrent prostate carcinoma scanned with 68 Ga-PSMA-11 PET/CT and showed changes in the radiotherapy plan in 56.6% (22). These consistent results are also supported by numerous other studies supporting the role of 68 Ga-PSMA-11 PET/CT in this setting (11,12,23,24). 68 Ga-PSMA-11 PET/CT imaging identification of isolated bone metastases has led to an increase in the use of stereotactic body radiation therapy, and the detection of small nodes often leads to increased use of simultaneous integrated boost to affected areas (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Schmidt-Hegemann et al reported 129 men with recurrent prostate carcinoma scanned with 68 Ga-PSMA-11 PET/CT and showed changes in the radiotherapy plan in 56.6% (22). These consistent results are also supported by numerous other studies supporting the role of 68 Ga-PSMA-11 PET/CT in this setting (11,12,23,24). 68 Ga-PSMA-11 PET/CT imaging identification of isolated bone metastases has led to an increase in the use of stereotactic body radiation therapy, and the detection of small nodes often leads to increased use of simultaneous integrated boost to affected areas (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…In our 68 Ga-PSMA-11 PET/MRI cohort, we observed a considerably higher detection rate of 65% in patients presenting with PSA values between 0.2 and 0.5 ng/mL at the time of the scan. Published data on the detection rate in patients with even lower PSA values (,0.2 ng/mL) are scarce and include only small patient cohorts (18,19,22,23). Reported detection rates for this cohort with a very low PSA range between 33% and 47.1%.…”
Section: Discussionmentioning
confidence: 96%
“…Kabasakal et al [ 58 ] reported a PET positivity of 31% ( n = 4), 54% ( n = 13), and 88% ( n = 14) in patients with a PSA level of less than 0.2, 0.2–2, and 2–5 ng/ml, respectively. A positive correlation was also observed between positivity and GS.…”
Section: Recurrent Pc - “Secondary Staging”mentioning
confidence: 99%